Effect of Lifestyle Modification Intervention on Health Status of Coronary Artery Disease Patients: Randomized Control Trial (International Journal of Studies in Nursing, 2018)
Background: Coronary artery disease is a major cause of morbidity and mortality throughout the world. Modification of life style can be achieved by patients' education to improve their health status. Aim: To evaluate effect of lifestyle modification intervention on health status of coronary artery disease patients. Design: Randomized control trial used to achieve the aim of this study. Setting: The current study conducted at the coronary care unit and cardiology out-patient clinics of Benha University Hospital, Benha City. Subjects: Purposive sample of 92 coronary artery disease patients (study and control) were included in the study. Tools: Two tools used in this study 1) Interview questionnaire. 2) Health status questionnaire. Results: Significant percentage of the study participants from both groups were adhered to unhealthy life-style practices as smoking, eating salty and fatty foods, drinking tea and coffee as well as they didn't practice exercises and recreational activities. After lifestyle modification intervention, there were significant statistical differences between the two groups favoring the study group regarding all aspects of health status; physical function, bodily pain, social function, role limitation due to physical or emotional problems and mental health (P